2006
DOI: 10.1177/0146167205276431
|View full text |Cite
|
Sign up to set email alerts
|

Intergroup Reconciliation: Effects of Adversary's Expressions of Empathy, Responsibility, and Recipients' Trust

Abstract: The present study explores the effects of expressions of empathy for the ingroup's conflict-related suffering and assumed responsibility for causing it by a representative of the rival outgroup on recipient's willingness for reconciliation. It is suggested that such positive expressions by an adversary will have positive effects on reconciliation only in the presence of a basic level of trust in the outgroup. In two studies, Israeli-Jewish participants were exposed to a Palestinian leader who either expressed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
302
1
5

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 296 publications
(331 citation statements)
references
References 23 publications
23
302
1
5
Order By: Relevance
“…The present study focuses on two other key antecedents identified in the literature: intergroup trust (Hewstone et al, 2006) and inclusive perceptions of victimhood (acknowledging that both sides have experienced victimization, Vollhardt, 2009;2013), shown in previous research to affect Israeli Jews' forgiveness tendencies Liviatan, 2006, andNoor, 2013, respectively). We aimed to replicate and extend these findings by testing the role of trust and inclusive victim perceptions in promoting forgiveness as well as consequent peace vision endorsement.…”
Section: Trust and Inclusive Victim Perceptions As Antecedents Of Formentioning
confidence: 99%
“…The present study focuses on two other key antecedents identified in the literature: intergroup trust (Hewstone et al, 2006) and inclusive perceptions of victimhood (acknowledging that both sides have experienced victimization, Vollhardt, 2009;2013), shown in previous research to affect Israeli Jews' forgiveness tendencies Liviatan, 2006, andNoor, 2013, respectively). We aimed to replicate and extend these findings by testing the role of trust and inclusive victim perceptions in promoting forgiveness as well as consequent peace vision endorsement.…”
Section: Trust and Inclusive Victim Perceptions As Antecedents Of Formentioning
confidence: 99%
“…After providing their informed consent, they completed a two-part questionnaire that was presented to them as a survey on attitudes related to media communication (for a similar procedure used in the same context see Nadler & Liviatan, 2006;Shnabel, Nadler, Ullrich, Dovidio, & Carmi, 2009). …”
Section: Methods Participants and Designmentioning
confidence: 99%
“…Further, in the absence of trust, conciliatory gestures by the rivals may be perceived as driven by instrumental intentions. For example, Nadler and Liviatan (2006) showed that for IsraeliJews with low levels of trust toward Palestinians the empathic message from a Palestinian leader had a "boomerang effect" by decreasing their willingness to reconcile with outgroup members. In considering the conflictual relation between the two main linguistic communities in Belgium, Alarcón-Henríquez and colleagues (2010) also showed that high-trusting -but not low-trusting -Dutch-speaking participants displayed positive attitudes toward their French-speaking counterparts when the latter acknowledged the importance of shared past sufferings.…”
Section: Intergroup Trust In Conflictual Settingsmentioning
confidence: 99%
See 2 more Smart Citations